Understanding the drivers of rural household scaling up of integrated crop-livestock-forestry systems. A systematic review and bibliometric analysis - Kotobiodjo, Mahugnon Néhémie; Egah, Janvier; Dato, Stéphenson Marcel; Baco, Mohamed Nasser (Frontiers in Sustainable Food Systems, 2024)
This literature review focuses on the drivers of Integrated Crop-Livestock-Forestry Systems (ICLFS) adoption by small farmers. It has enabled us to identify current trends and analyze the various drivers of adoption and knowledge gaps. According to the PRISMA literature review protocol, 1,352 scientific publications have been selected and analyzed after a Scopus database search. Data analysis was carried out in two steps. A systematic review was performed with the metadata of scientific publications using the Biblioshiny package of R 4.3.1 software. Then, the 42 most relevant publications were used for a brief narrative synthesis. The results showed that between 2003 and 2023, publications were made in 587 different sources. 73% of publications were scientific articles. 91% of publications were written by an average of 05 co-authors. The effectiveness of Integrated Crop-Livestock-Forestry Systems (ICLFS) practices, the production of organic matter and the effects on farmers’ livelihoods are the research topics considered. Five categories of factors were identified to facilitate the adoption of ICLFS by small farmers: (i) farmer profile, (ii) farm characteristics, (iii) economic factors, (iv) institutional factors and (v) biophysical factors. Policy orientations are the most decisive of all the factors identified, followed by the establishment of extension systems and social networks between farmers. This paper makes three main recommendations. Firstly, it recommends the implementation of collaborative research frameworks between West African researchers and those from East Africa, Asia and South America, who have more experience in this area. In addition, this study suggests that future research on the adoption of ICLFS should take into account herd mobility issues in the adoption process. Finally, it suggests that ICLFS should be taken into account in development policies and implemented through action research projects, mostly in West Africa.